The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/pr7080543
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Entities in the Mining Industry by Optimizing Green Business Processes and Emission Inventories

Abstract: Due to environmental considerations, environmental sustainability has become the main target of contemporary organizations, which has a direct influence on increasing their performance. The purpose of this study was to present the efficiency of green business process optimization for the performances of mining entities. Quantitative research was carried out on a sample of 209 people in an economic entity in the mining industry. The results of the study indicated real possibilities to achieve the objectives set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…A similar study has also been performed in Thailand wit the companies certified with ISO 14001, and the result indicated that green supply chai management implementation affects the environmental, economic, and intangible perfo mance of the companies [4]. Research by [64] in the Romanian mining entities has show that firm performance could be improved by optimizing the green business strategy an emission inventories. Based on the above arguments, the last hypothesis is determined a follow:…”
Section: Relationship Between Green Supply Chain Management and Firm Performancementioning
confidence: 83%
“…A similar study has also been performed in Thailand wit the companies certified with ISO 14001, and the result indicated that green supply chai management implementation affects the environmental, economic, and intangible perfo mance of the companies [4]. Research by [64] in the Romanian mining entities has show that firm performance could be improved by optimizing the green business strategy an emission inventories. Based on the above arguments, the last hypothesis is determined a follow:…”
Section: Relationship Between Green Supply Chain Management and Firm Performancementioning
confidence: 83%
“…In terms of green business, the company does not only have its own internal processes; at the same time, it chooses its suppliers and subcontractors according to the adoption of similar truths. Green management is an approach that encompasses the entirety of a company's internal and external relations (Oncioiu et al, 2019). Green business has a perspective that covers all functions of a business.…”
Section: Conceptual Framework About Green Business Issues Green Econo...mentioning
confidence: 99%
“…Namely, with the green management approach, there will be an increase in the sales profitability of the enterprises and a decrease in the production costs. While companies' implementation of renewable energy or savings policies with an environmentalist approach will reduce their costs, there will be an increase in sales profitability with the increase in social awareness (Oncioiu et al, 2019).…”
Section: Green Human Resourcesmentioning
confidence: 99%
“…Entrepreneurial education becomes a support for environmental aspects. Oncioiu et al analyzed the possibility of modifying business processes in the green field and regarded the effectiveness of these measures [29]. Another argument is provided by Cárcel-Carrasco et al, who analyzed the influence of industrial maintenance on the strategic planning of companies, concluding that it exists and resides in better economic results [30].…”
Section: Motivations For Entrepreneurship and Barriers For Young Entrepreneursmentioning
confidence: 99%